2021
DOI: 10.1080/15412555.2021.1899155
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Pertussis in COPD: A Retrospective Database Study in England

Abstract: Chronic obstructive pulmonary disease (COPD) may increase the risk and severity of pertussis infection. Health care resource utilization (HCRU) and direct medical costs (DMC) of treating pertussis among patients with COPD are unknown. Reported incidence of pertussis among individuals aged ! 50 years with COPD was assessed in Clinical Practice Research Datalink and Hospital Episode Statistics databases during 2009-2018 using a retrospective cohort design. HCRU and DMC from the National Health Service perspectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Other complications are less frequent and include seizures and encephalopathy (cerebral hypoxia related to asphyxia), subarachnoid and intraventricular haemorrhages, and tetanic seizures [ 45 ]. Individuals with underlying conditions, such as asthma, chronic obstructive pulmonary disease (COPD), and obesity are at an even higher risk to develop a severe form of the disease [ 46 48 ], and recent studies suggest that pertussis incidence in COPD populations may be grossly underestimated [ 49 , 50 ]. Pertussis has been associated with an increase in healthcare resource use in patients with COPD and asthma, increasing the overall economic burden, exacerbation, and hospitalisation rate related to the disease [ 51 53 ].…”
Section: Burden Of Pertussis In Adultsmentioning
confidence: 99%
“…Other complications are less frequent and include seizures and encephalopathy (cerebral hypoxia related to asphyxia), subarachnoid and intraventricular haemorrhages, and tetanic seizures [ 45 ]. Individuals with underlying conditions, such as asthma, chronic obstructive pulmonary disease (COPD), and obesity are at an even higher risk to develop a severe form of the disease [ 46 48 ], and recent studies suggest that pertussis incidence in COPD populations may be grossly underestimated [ 49 , 50 ]. Pertussis has been associated with an increase in healthcare resource use in patients with COPD and asthma, increasing the overall economic burden, exacerbation, and hospitalisation rate related to the disease [ 51 53 ].…”
Section: Burden Of Pertussis In Adultsmentioning
confidence: 99%
“…5 The overall incidence of laboratory confirmed pertussis cases across all age groups in England in 2019 was 7 per 100,000 population 6 (approximately 5 notifications per 100,000 among those aged ≥45 years), 5,7 but seroprevalence studies from Europe indicate that the true rate of pertussis infection could be hundreds or even thousands of times higher than the reported incidence. [8][9][10] Data from patients with chronic obstructive pulmonary disease (COPD) in England also support this under-recognition, as the rate of diagnosed pertussis was approximately 5 per 100,000 in 2013, 11 but a seroprevalence study in the same year indicated that 5.8% of COPD patients had antibody levels indicative of exposure to B. pertussis in the past year. 12 Pertussis is particularly under-recognized or misdiagnosed in adults, 13,14 possibly because health care providers often view pertussis as a childhood disease, 15 instead suspecting acute bronchitis or simply "cough", 16 also because adults can be asymptomatic 17 or present with mild or atypical symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…3 Patients with asthma or COPD have also been reported to incur higher health care resource utilization (HCRU) and direct medical costs (DMC) 21 than those with pertussis alone. Among adults with COPD, a diagnosis of pertussis has been associated with higher HCRU and DMC, 11 but the additional burden of asthma and pertussis compared to asthma alone has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…For example, seasonal influenza infection in people with pre-existing circulatory or respiratory disease may result in their hospitalization or death [61]. Adults aged more than 50 years and who have HZ are at increased risk of asthma, heart disease, stroke, and transient ischemic attack [12,13,[62][63][64], while pertussis infection is likely to increase the severity of symptoms in patients with pre-existing asthma or COPD [14][15][16].…”
Section: The Unfavorable Link Between Infectious and Chronic Diseasesmentioning
confidence: 99%
“…Chronic diseases in older adults are more difficult to treat in the presence of infectious diseases. Infectious diseases may induce cardiovascular complications, increase the risk of heart disease, and worsen asthma or chronic obstructive pulmonary disease (COPD) symptoms [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%